Impact of Gut Microbiota and Microbiota-Related Metabolites on Hyperlipidemia - Jia, Xiaokang; Xu, Wen; Zhang, Lei; Li, Xiaoyan; Wang, Ruirui; Wu, Shuisheng (Frontiers in Cellular and Infection Microbiology, 2021)
Hyperlipidemia, defined as the presence of excess fat or lipids in the blood, has been is considered as a high-risk factor and key indicator of many metabolic diseases. The gut microbiota plays a vital role in regulating host lipid metabolism, and its dysbiosis contributes to the pathogenesis of hyperlipidemia. The effector mechanism of microbiota-derived metabolites such as bile acids, lipopolysaccharide, and short-chain fatty acids in the regulation of hyperlipidemia has been partially unveiled. Studies on gut-microbiota-targeted hyperlipidemia interventions, including the use of prebiotics, probiotics, fecal microbiota transplantation, and natural herbal medicines, have shown their efficacy in hyperlipidemia treatment. In this review, we summarize the relationship between gut microbiota and hyperlipidemia, the impact of gut microbiota and microbiota-derived metabolites on the development and progression of hyperlipidemia, and the potential therapeutic management of hyperlipidemia targeted at gut microbiota.